Effect of Antimicrobial Peptide BiF2_5K7K on Contaminated Bacteria Isolated from Boar Semen and Semen Qualities during Preservation and Subsequent Fertility Test on Pig Farm - Krittika Keeratikunakorn; Panida Chanapiwat; Ratchaneewan Aunpad; Natharin Ngamwongsatit; Kampon Kaeoket (MDPI AG, 2024)
The purpose of this study was to determine the impact of an antimicrobial peptide, BiF2_5K7K, on semen quality and bacterial contamination in boar semen doses used for artificial insemination. A key factor affecting semen quality and farm production is bacterial contamination in semen doses. Using antibiotics in a semen extender seems to be the best solution for minimizing bacterial growth during semen preservation. However, concern regarding antibiotic-resistant microorganisms has grown globally. As a result, antimicrobial peptides have emerged as interesting alternative antimicrobial agents to replace the current antibiotics used in semen extenders. BiF2_5K7K is an antimicrobial peptide that can inhibit Gram-negative and Gram-positive bacteria isolated from boar semen and sow vaginal discharge. In this study, ten fresh boar semen samples were collected and diluted with one of two types of semen extender: with (positive control) or without (negative control) an antibiotic (i.e., gentamicin). The semen extender without an antibiotic contained antimicrobial peptide BiF2_5K7K at different concentrations (15.625, 31.25, 62.5, and 125 µg/mL). The samples were stored at 18 °C until use. Semen quality parameters were assessed on days 0, 1, 3, and 5, and the total bacterial count was also evaluated at 0, 24, 36, 48, and 72 h after storage. A fertility test on a pig farm was also performed via sow insemination with a commercial extender plus BiF2_5K7K at a concentration of 31.25 µg/mL. No significant difference was found in terms of semen quality on days 0 or 1. On days 3 and 5, the total motility, progressive motility, and viability remained normal in the 15.625 and 31.25 µg/mL groups. However, the sperm parameters decreased starting on day 3 for the 125 µg/mL group and on day 5 for the 62.5 µg/mL group. For total bacterial count at 0, 24, 36, 48, and 72 h, the lowest bacterial count was found in the positive control group, and the highest bacterial count was found in the negative control group compared with the other groups. Comparing antimicrobial peptide groups from 0 to 48 h, the lowest bacterial count was found in the 125 µg/mL group, and the highest bacterial count was found in the 15.625 µg/mL group. For the fertility test, artificial insemination was conducted by using a commercial extender plus BiF2_5K7K at a concentration of 31.25 µg/mL. The results showed a superior pregnancy rate, farrowing rate, and total number of piglets born compared with artificial insemination conducted using a commercial extender plus antibiotic. In conclusion, BiF2_5K7K can inhibit bacterial growth in extended boar semen for 24 h, and thereafter, the bacterial count slightly increases. However, the increase in the number of bacterial counts from days 0 to 3 had no negative effect on sperm quality in the positive control, 15.625, or 31.25 µg/mL groups. This indicates that BiF2_5K7K might be an antimicrobial peptide candidate with potential for use as an alternative antimicrobial agent to replace the conventional antibiotic used in boar semen extenders.